Pengembangan Model Bahan Ajar Merancang Karya Ilmiah Berbasis Kontekstual - Zelika Zelika; Yohana Satinem; Dian Ramadan Lazuardi (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2020)
This study aims to design teaching material products to design scientific papers through a contextual approach that is valid, practical, and effective. The method used is Research and Development. The results showed that the teaching materials for designing contextual-based scientific work for the 2018/2019 academic year were in accordance with what was expected, namely having a teaching material book that had complete material and was in accordance with the needs of students. The results of this study have also been valid by getting a percentage of all validators, namely 81% with a very good category, the practicality of teaching materials in designing contextual-based scientific work gets a percentage of 82.5% with a very good category and the effectiveness of teaching materials for writing official letters gets an average percentage 80.1% with a very good category. In conclusion, the teaching materials for designing scientific work that the researchers have developed are valid, practical and effective. Keywords: Contextual Based, Designing Scientific Work, Learning Material Development